An ultralow specific on-resistance bidirectional trench power MOSFET with RESURF stepped oxide. (February 2023) - Fang, Dong; Liu, Wenliang; Qiao, Ming; Long, Xingrui; Qi, Zhao; Zhang, Bo
Abstract: This paper presents an ultralow specific on-resistance ( R on, sp ) bidirectional trench power metal-oxide-semiconductor field effect transistor (MOSFET) with RESURF stepped oxide (RSO) for lithium-ion (Li-ion) battery protection circuit application. Compared with the conventional dual die bidirectional switches, the proposed single die structure almost halves the total die area with the same cell pitch. Moreover, the drift region under reverse blocking condition is a 2-D depletion and due to the RSO-assisted depletion effect, the concentration of the drift region under reverse blocking condition can be approximately increased by one order, thus a smaller on-state resistance is obtained. Besides, the parasitic transistor is well suppressed due to the cathode short structure for forwardly and a breakdown margin for reversely blocking conditions, respectively. Consequently, based on the analytical design and simulation, the novel single die bidirectional switch ultimately achieves an ultralow R on, sp of 1.84 mΩ⋅mm 2 with a bidirectional breakdown voltage ( V B ) of 20 V, which has a better figure of merit (FOM).